Distribution and seasonality of the marine macrophytes from Antikyra Gulf (Viotia, Greece) - MALEA, P.; HARITONIDIS, S. (Mediterranean Marine Science, 2001)
The Gulf of Antikyra (Viotia) with a bauxitic substrate was aggravated by wastes discharged from an Aluminium factory where the Parnassos bauxite is treated Seasonal collections of macrophytes from stations selected inside the Antikyra Gulf were carried out. 85 species of macroalgae were totally collected, out of which 16 belonged to Chlorophyceae, 12 to Phaeophyceae and 57 to Rhodophyceae. There has been no obvious difference in the qualitative composition of the macroalgae as we move away from the area where the wastes are being discharged. Moreover, the stations where depths are greater exhibit different qualitative composition that those with smaller depths. The presence of phanerogams and especially that of Halophila stipulacea, the Lessepsian immigrant, encountered for the first time in the Korinthiakos Gulf, was also evident. The biomass of the three phanerogams decreased with the order: Posidonia oceanica>Cymodocea nodosa>Halophila stipulacea. The biomass of C. nodosaand P. oceanica was higher in July, while that of H. stipulacea was lower in July and higher in March and September.